Survey of Gross Motor Skills in Students with Intellectual Disabilities Aged 6-10 Years at SLBN C Pembina Malang - Edo Ferdiansyah; Rama Kurniawan; Herdhika Ayu Retno Kusumasari (Universitas Negeri Malang, 2024)
This research was conducted because of the lack of understanding of motor skills in children with disabilities. This study aims to evaluate and understand the level of gross motor skills of students with tunagrahita in SLBN C Pembina Malang Regency. The method used was a quantitative descriptive survey, with purposive sampling of the sample that considered the criteria of student age between 6 to 10 years. To measure students' gross motor skills, the TGMD-2 (Test of Gross Motor Development-2) tool was used (Ulrich, 2000). The sample of this study involved 9 students from SLB and 23 students from primary school. The results of this study show that the gross motor skills of children with disabilities are at a very low level, so it is necessary to develop a special education programme focused on improving the gross motor skills of children with disabilities. In addition, these results also show the importance of improving professional skills and understanding of the methods of measuring motor abilities in children with special needs intellectual disability in SLBN C Pembina Malang Regency.